COVID-19 and their outcomes: how personality, place, and sex of people play a role in the psychology of COVID-19 beliefs. (3rd August 2021) - Brito-Costa, Sonia; Jonason, Peter K; Tosi, Michele; Antunes, Rui; Silva, Sofia; Castro, Florêncio
Abstract: Background: There is considerable variation in people's attitudes towards the COVID-19 pandemic. One way to understand why people differ in their attitudes is to examine how personality traits predict the degree to which people hold different attitudes. Methods: We collected data ( N = 1420) from Portugal and Spain using Facebook advertising. We measured the Dark Triad and Big Five traits, and negative affect, along with ad hoc items for religiousness, and attitudes towards and fear of COVID. Results: Neuroticism and Negative affect was linked to various domains of insecurity or fear and provides insights into how personality predicts concerns and behaviors related to the COVID-19 pandemic. Religious people were less trusting in science, thought prayer was answer, and attributed the existence of the virus to an act of God. Women reported more fear of COVID-19 than men did, and this was enabled by women's greater tendency to have Negative Affect and higher Neuroticism than men. Conclusions: Neurotic people and those with more Negative Affect appear to be more fearful, more trusting in others and systems likely to protect them (e.g., scientists), and less likely to trust in systems shown to not help them (e.g., prayer). We found other effects for the Dark Triad traits and the Big Five traits. In total, we highlight some of the reasons that people may be in such disagreements about what to do about the virus at the individual and institutional levels. Personality, place, and participant's sex all appear to play a role in the psychology of COVID-19 beliefs.